Interdependence of Political and Media Process in Russia: Current Problem State - BALYNSKAYA, Natalya Rinatovna (Journal of Advanced Research in Law and Economics; Vol 6 No 3 (2015): JARLE Volume VI, Issue 3(13), Winter 2015, 2017)
This article examines the role of information in the political process. Patterns and interrelationships of these processes are analyzed, and the necessity of correct and timely information support of political events is revealed and grounded. It was found on the basis of the study that the information should be considered as a necessary condition underlying any political event. This implies that the political and media processes in Russia are closely interconnected. The author also raises the question of the subjects of political interactions, since the traditional Russian political science does not recognize an individuality as an independent subject: it is concluded that the subjects taking part in politics, as a rule, are a group (this presentation includes a political party), while an individual as an individuality is considered in political science only as a political leader. The author of the article concludes that this state of affairs in the mass-media era is changing, since an individual possessing information resource may also play an important role in politics. This is especially evident at the level of municipal government, where recognition of individuals is large, compared to the federal level.